Analisis Biaya Produksi Usaha Rintisan Budidaya Maggot Pada Kelompok Petani Tambak Kelurahan Mangunharjo, Semarang - Oktavia, Vicky; Shalahuddin, Sultan Tegar; Setyahuni, Suhita Whini; Samasta, Almira Santi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Mangunharjo Subdistrict, Tugu District, Semarang City, has significant potential for the development of pond-based fisheries enterprises, particularly milkfish cultivation. However, fishpond farmers face a major challenge in the form of high commercial feed costs, which constitute the largest component of production expenses and result in low business efficiency. To address this issue, more economical and easily applicable alternative feed sources are required. This community service activity aims to enhance the capacity of fishpond farmers through training programs focusing on maggot cultivation as an alternative feed and improving their understanding of production cost analysis. The implementation methods include field observations, training sessions, Focus Group Discussions (FGD), and direct assistance to fishpond farmer groups. The results indicate an improvement in participants’ knowledge and skills in producing and utilizing maggots as a substitute for commercial feed, as well as their ability to manage and reduce production costs more efficiently. Furthermore, the activity encourages positive changes in farmers’ mindset and behavior toward more independent and sustainable business management. This program is expected to serve as an initial step in strengthening start-up maggot cultivation enterprises as a solution for reducing production costs and improving the welfare of fishpond farmers